Work Life Balance as A Moderating Variable of The Effect of Reward on Employee Performance - Imelda Barus; Rasty Yulia; Rizal Bakti; Faisal Angriawan Malik; Desi Ulpa Anggraini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research is quantitative with an explanatory approach. The data used in this study is primary data obtained directly by the researcher from Geprek Bensu employees spread throughout Indonesia. The data obtained was analyzed using PLS 4.0 software. The reult in this article show that that each hypothesis in this article can be accepted and proven. In the first hypothesis, the Reward variable can have a positive relationship and a significant influence on Employee Performance because the P-Values ​​are positive and below the 0.05 significance level, namely 0.002. These results mean that Rewards can make employees happier and more enthusiastic at work. With more enthusiasm and happiness in their work, it will improve Employee Performance. In addition, the Work-Life Balance variable can also moderate the influence of the Reward variable on Employee Performance because the P-Values ​​are positive and below the 0.05 significance level, namely 0.000. Based on this, the first and second hypotheses in this article can be accepted and proven